Effect of ZrSiO₄ Reinforcement and Processing Parameters on the Texture Evolution and Microstructure of Fe and Al Matrix Composites - Sanaa Masod Abdulqader; Najah Ibrahem Elharari, (Al-imad Journal of Humanities and Applied Sciences (AJHAS), 2026)
This research investigates the crystallographic texture and microstructural evolution of iron (α-Fe) and aluminum (Al) matrix composites reinforced with zircon (ZrSiO4) particles at concentrations of 0.2 and 0.4 wt%. The study evaluates the influence of mechanical surface treatment and sintering duration (1h and 4h) on the crystal structure using X-ray Diffraction (XRD). Texture coefficients (TC) calculated via the Harris method confirm a strong preferred orientation in the samples. Results demonstrate that for BCC iron, surface polishing is the dominant control factor; non-polished samples exhibit a strong 110 texture with TC (110) = 3.00, while polishing significantly reduces this value. Conversely, for FCC aluminum, processing time is the primary control factor, where extended sintering to 4 hours triggers a texture switch from the 311 to the 200 planes, resulting in a strong 200 texture with TC (200) = 3.00. Furthermore, ZrSiO4 additions act as effective grain refiners, decreasing crystallite size from 62 nm to 38 nm in the iron matrix and increasing lattice strain from 0.11% to 0.25%, as determined by the Scherrer equation and Williamson-Hall method. While these additions modify diffraction intensity and microstructural features, they do not alter the texture coefficient values. These findings provide a scientific baseline for optimizing sintering conditions to tailor the anisotropic properties of metal-ceramic composites for structural applications.
Keywords: X-Ray Diffraction; Crystallographic Texture; Iron; Aluminum; Zircon; Surface Treatment; Texture Coefficient; Harris Method; Scherrer Equation; Lattice Strain